Approximation of an Additive ϱ1, ϱ2-Random Operator Inequality. (18th February 2020) - Jang, Sun Young; Saadati, Reza
Abstract : We solve the additive ϱ 1, ϱ 2 -random operator inequality ξ t T ω, u + v − T ω, u − T ω, v ≥ κ M ξ t ϱ 1 T ω, u + v + T ω, u − v − 2 T ω, u, ξ t ϱ 2 2 T ω, u + v / 2 − T ω, u − T ω, v, in which ϱ 1, ϱ 2 ∈ ℂ are fixed and max 2 ϱ 1, ϱ 2 < 1 . Finally, we get an approximation of the mentioned additive ϱ 1, ϱ 2 -random operator inequality by direct technique.